Managing price volatility in an open economy environment: the case of edible oils and oilseeds in India - Srinivasan, P. V. (International Food Policy Research Institute, 2004)
This study examines the impact of alternative price stabilization policies for edible oils and oilseeds in India on the farmers growing oilseeds, the consumers of edible oils and the processing sector with the help of a multi market equilibrium dynamic simulation model. Price stability in the edible oil sector is important at least for two reasons. It can help realize the growth potential in the production of edible oils and improve the nutritional security of Indian households. While efficiency considerations suggest the linking of domestic to world prices, extreme fluctuations in price have to be avoided, for they can lead to undesirable consequences both at the macro and micro levels. The questions addressed in this study include the following. What is the effectiveness of alternative price stabilization mechanisms in stabilizing oilseed/ edible oil prices? Can variable levies that vary within the bound tariff level provide adequate protection against world price fluctuations? What are the costs to the government, benefits to producers and consumers? What is the impact on prices of oilseeds due to the operation of variable levies edible oil imports and vice versa? -- From Author's Executive Summary